Finnish female coaches' career development and perceptions : a case study of six Finnish female coaches - Olkinuora, Hanna (2016)
Women are often seen as needing to be good at everything and sometimes even better. The numbers of women and girls participating in sport are growing rapidly. However, the same pattern cannot be observed in the leadership positions within sport, which includes coaches. Although the field of female leadership within sport organizations has been researched, what factors influence female coaches’ career paths and the reasons behind the under representation is still under researched in Finland.